Artificial intelligence as a teaching tool in university education - Reina Marín, Yuri; Cruz Caro, Omer; Maicelo Rubio, Yecenia del Carmen; Alva Tuesta, Judith Nathaly; Sánchez Bardales, Einstein; Carrasco Rituay, Angelica María; Chávez Santos, River (Frontiers in Education, 2025)
Artificial intelligence (AI) has become a key factor in higher education, revolutionizing both teaching methods and student learning. This study aimed to identify the perceptions of university students and professors on the use of AI in academic education. A descriptive study with a quantitative approach was conducted using the deductive method and a Likert scale questionnaire. The results revealed a predominantly low perception of AI in university teaching, with 71.5% of students and 73.1% of professors expressing skepticism about its application. Additionally, 59% of students and 65.9% of professors evaluated the impact of AI on the learning process unfavorably, indicating concerns about its effectiveness in enhancing education. Ethical and privacy considerations showed a contrast, with 84% of students displaying high confidence while 73.2% of professors maintaining moderate trust. These findings highlight a perception gap and a lack of confidence in assessing the impact of AI, emphasizing the urgent need for training programs, comprehensive policies, and evaluation methodologies. Addressing these concerns is crucial for harnessing AI’s potential in higher education and preparing students and professors for an increasingly digitized academic environment.